STUDY OF SUGAR CANE SUGAR AGROINDUSTRY MECHANICAL METHODS AND CONVENTIONAL METHODS: A COMPARISON OF INCOME - Mira Wati Yanita; Ira Wahyuni (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2021)
Cane sugar agroindustry is the processing of sugarcane juice into sugar cane using conventional methods. However, along with the development of this agroindustry innovation began to adopt technology with mechanical methods. In the production process, there is the use of inputs that differentiate the impact on agroindustry income which is not yet known for certain, therefore this study aims to: 1) determine the description of the sugar cane agroindustry method mechanical and conventional methods at Kayu Aro, Kerinci District, 2) knowing the comparative income of sugar cane agroindustry with mechanical and conventional methods at Kayu Aro, Kerinci District. This research was conducted on August 10th to September 10th, 2020 at Sungai Asam Village, Kayu Aro, Kerinci District purposively, with the consideration that Sungai Asam Village has the largest area of sugarcane land, sugarcane production, sugar production and the largest number of craftsmen and there are more processing methods from one. The number of samples was 47 people, divided into 33 mechanical craftsmen and 14 conventional craftsmen. The data analysis method used is descriptive analysis, income analysis and comparative analysis of sugar cane agroindustry income with a two difference test mean. (1) The difference in the methods used causes the difference in the amount of sugarcane juice raw material produced by the mechanical method is greater which affects the amount of use of auxiliary materials and the fuel needed is also greater which results in higher sugar production than conventional. So that mechanical processing is better than conventional processing. (2) The income of the mechanical method of cane sugar agroindustry is 40% higher than conventional. This occurs as a result of the difference in the amount of bulk sugar production which is greater than the sugar production at different price levels.Keywords: Sugar Cane, Mechanical, Conventional, Income, Comparison